PREDICTION BACKUP TESTICULAR FUNCTION IN PATIENTS WITH NONOBSTRUCTIVE AZOOSPERMIA - N. G. Kul’chenko (Issledovaniâ i Praktika v Medicine, 2016)
Modern authors believe that male infertility accounts for 40–50%. The most severe form of male infertility is azoospermia, which is observed in 10–15% of cases. The only method of diagnosis of azoospermia is testicular biopsy, which allows not only to differentiate the secretory and excretory forms of infertility, but also to determine the degree of impairment of spermatogenesis.Purpose. To improve the diagnosis of male infertility.Materials and methods. We have examined 26 men with non-obstructive azoospermia (according to semen). The comparison group included healthy men – 22 people. Patients underwent biopsy of the testicle, followed by morphological analysis of biopsies. Sections of testicular tissue was stained with hematoxylin and eosin, indirect immunohistochemical studies – definition of Inhibin B, a protein prolife ration and apoptosis (ki-67)Results. According to clinical and instrumental examination (ultrasound) we found no abnormalities. Patients set idiopathic form of infertility. When painting testice slices with hematoxylin and eosin, we recorded significant changes in the convoluted seminiferous tubules in patients with azoospermia: the diameter is reduced to 1.5–2 times (hypoplasia), the basement membrane with a strong fiber component (fibrosis) (p < 0,05). Expressed Inhibin tissue expression observed in Sertoli cells (“+++”) and to a lesser extent in spermatogonia ( «±»), located closer to the basal membrane convoluted seminiferous tubule. The expression level of Inhibin in germ cells - up to 5%. ki-67 protein expression was observed in the nuclei (S-phase of mitosis) spermatogonia (“++”) at stages II and III and spermatogenesis in some primary nuclei (“+”) and secondary (“+”) spermatocytes. Expression of ki-67 level in the germ cells – up to 25%.Conclusion. Determination of tissue levels of Inhibin-B can be used as a p rognostic test backup testicular function.